Self-Islah, Gender Relation and Socio-Economic Challenges on Tablighi Jamaat Proselytization Practice in Indonesia - Saipul Hamdi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This article explores one of the Tablighi Jamaat (TJ) teachings self-islah that develops in its dawah practices.Self-Islah emphasizes improving oneself through a proselytization program called khuruj from one community toanother, from one mosque to another. All this time, dawah was used as a medium to improve and correct others byMuslim priest (da’i) without being directly involved in the practice of islah. The phenomenon of JT dawah showsa different approach and pattern where da’i play dual roles not only as subject (preachers) but also as an object(listeners) during that khuruj program. Self-islah in this context includes strengthening faith, morals, and genderawareness. The gender aspect is strong external critics of JT religious tradition where it does not involve women intheir religious activities and even avoids interacting with them. Thus, TJ members must handle all the needs whilestaying in the mosque for religious camps, such as washing clothes, cooking, washing dishes, and serving guestsfrom the local and international community. The article will investigate changes in gender relations within the JTfamily in the post-khuruj program. This article also focuses on the economic challenges faced by Tablighi memberswhen they go out of preaching (khuruj), especially those from the lower-middle class. They struggle to fulfill theneeds during dawah and the family's needs who left at home, especially for long periods such as 40 days, threemonths, and one year.